The Authority of the Party Court in Resolving Internal Disputes of Political Parties in Indonesia (A Case Study of Golkar Party) - Suparto Suparto (LEGAL BRIEF, 2022)
In its development, political parties as organizations are always faced with a conflict that often leads to divisions. On that basis, the internal party settlement is then regulated in the political party law. In Law no. 2 of 2011, it is stated that the resolution of internal conflicts of political parties related to management is resolved by the Party Court and the decision is final. However, many conflicts that occur in political parties are not resolved, for example as happened to the Golkar Party. The research method uses normative juridical with a statutory approach. Based on the results of the study, there are several influential factors in the resolution of internal disputes within the Golkar party, including: 1. The unusual and multi-interpreted form and format of the decision from the Golkar Party Court does not solve the problem of internal disputes in the management of the Golkar party, 2. There is a tendency for the government to intervene in the internal affairs of political parties, in this case the Golkar party, by acknowledging one of the parties close to or supporting the government in the form of ratification of the management of political parties, 3. The neutrality of the membership of the Party Court from internal political parties is doubtful and there is a tendency to side with one of the disputing parties. 4. The even number of members of the Party Court when hearing the dispute over the management of the Golkar party